Adsorption of Cadmium (II) and Chromium (VI) from Aqueous Solution by Waste Marigold Flowers - Mondal, Monoj K.; Mishra, Garima; Kumar, Pradeep (International Centre for Sustainable Development of Energy, Water and Environment Systems SDEWES, 2015)
In this work, waste marigold flowers from Temple were used as adsorbent to remove cadmium (II) and chromium (VI) ions from aqueous solutions. Influences of initial heavy metal concentrations, contact time, adsorbent dose, temperature and initial pH on removal of cadmium (II) and chromium (VI) ions were studied under batch mode of operation. Both the adsorption process of cadmium (II) and chromium (VI) followed pseudo-second order kinetics. Adsorption isotherm parameters of cadmium (II) and chromium (VI) on dried marigold flower were determined using Langmuir and Freundlich models. Thermodynamic parameters depicted that the process was spontaneous and exothermic under experimental conditions. The maximum removal efficiency of cadmium (II) was obtained as 83% at contact time 75 min and pH 5. The maximum removal efficiency of chromium (VI) was found as 96% at contact time 105 min and pH 3. Dried marigold flower showed active reusability characteristics upto three consecutive adsorption-desorption cycles.
Keywords: Adsorption; Cd(II) and Cr(VI); Isotherms; Kinetics; Marigold flower